Quality control of Ganoderma lucidum by using C, H, O, and N stable isotopes and C and N contents for geographical traceability - Zhang, Ying; Jiang, Kunxia; Chen, Sisi; Wang, Lina; Zhang, Xun; Xu, Wen; Yam, Mun Fei; Wu, Changhui; Xu, Wei; Lin, Yu (Frontiers in Plant Science, 2023)
Rationale: Ganoderma lucidum (G. lucidum) is a popular medicinal fungus used in traditional medicine for decades, and its provenance influences its medicinal and commercial worth. The amount of active ingredients and the price of G. lucidum from different origins vary significantly; hence, fraudulent labeling is normal. Reliable techniques for G. lucidum geographic verification are urgently required to safeguard the interests of consumers, producers, and honest dealers. A stable isotope is widely acknowledged as a useful traceability technique, and could be developed to confirm the geographical origin of G. lucidum. Methods: G. lucidum from various sources and stages was distinguished by using δ 13 C, δD, δ 18 O, δ 15 N, C and N contents combined with chemometric tools. Chemometric approaches, including PCA, OPLS-DA, PLS, and FLDA models, were applied to the obtained data. The established models was used to trace the origin of G. lucidum from various sources or track various stages of G. lucidum. Results: In the stage model, the δ 13 C, δD, δ 18 O, δ 15 N, C, and N contents were considered meaningful variables to distinguish various stages (bud development, growth, and maturing) using PCA and OPLS-DA and validated by the PLS model